Evaluation of global DNA hypomethylation in human colon cancer tissues by immunohistochemistry and image analysis. Issue 5 (1st November 2000) - Hernandez-Blazquez, F J; Habib, M; Dumollard, J-M; Barthelemy, C; Benchaib, M; de Capoa, A; Niveleau, A
Abstract : BACKGROUND: Global hypomethylation of DNA is frequently observed in human tumours. This alteration is detected in early adenomas in colorectal tumorigenesis. Information is currently acquired after extraction of DNA from tissues, digestion with nucleases, and analysis by reverse phase chromatography, or treatment with restriction enzymes followed by gel electrophoresis analysis and Southern hybridisation with radiolabelled probes. AIMS: The purpose of our work was to evaluate the global methylation status of DNA in malignant lesions without loosing the histopathological features of the samples. PATIENTS: The investigation was performed on paired normal-tumour tissues from 13 patients undergoing surgical resection of colorectal adenocarcinomas. METHODS: Antibodies raised against 5-methylcytidine can be used to label methyl rich regions in interphase nuclei. This technique was adapted to the study of paraffin embedded tissues and an immunohistochemical method was developed to assess the global methylation status of individual nuclei while preserving cell morphology and tissue architecture. Computer assisted quantification of the staining intensity was performed on malignant and normal zones of human colon tissues to test the correlation between the immunolabelling signal and the respective histological patterns observed. RESULTS: Qualitative and quantitative differences were observed and measured between the normal and malignant part of each sample. Morphologically altered nuclei displayed densely labelled spots within faintly labelled areas whereas normal nuclei were darker and uniformly stained. Image analysis allowed calculation of the average integrated optical density of the nuclei in both types of tissues, demonstrating a constant and significantly lower intensity for the former type of cells.